Implementation of RODE Learning Model: Improving Science Learning Outcomes of Junior High School - Arief Ertha Kusuma; Munirotunnisa; Ridwan; Rusmansyah; Shinta Wulandari (Postgraduate, University of Mataram, 2024)
This study aimed to determine the improvement of science learning outcomes by applying the RODE learning model. The subjects in this study were 19 students in the eighth grade of SMPN 3 Karang Intan in the even semester of the 2022/2023 academic year. Three observers assessed the RODE model implemented by the science teacher in her class on hydrostatics pressure material in the first cycle and Archimedes' law material in the second cycle. The Four pretest-posttest questions calculated the students' science learning outcomes. The success criterion of this study was that â‰¥ 75% of the research subjects obtained a score of â‰¥70. The data analysis used mode scores on observation data and pretest-posttest results for each cycle. According to the data analysis results, Teachers can apply the RODE learning model very well, with the mode score increasing from 3 in the first cycle to 4 in the second. 100% of students' science learning outcomes increased, with a mode score of 5 becoming 70 in the first cycle and a mode score of 30 becoming 100 in the second. Thus, the RODE learning model enhanced the science learning outcomes of eighth-grade students of SMPN 3 Karang Intan.